Fictions of Law: Criminality and Justice in the Juridical and Literary Imaginaries of Nineteenth-Century Argentina - Dorfman, Daniela (2018)
This article looks at the ways nineteenth-century Argentine literature articulates the relationship between the country’s inhabitants and the State and the law. It raises questions about how—in the context of the formation of the judicial and legal system and against the background of Rosas’s controversial regime and of laws that criminalised the gaucho—Argentine literature, itself in formation, represented and intervened in what Lawrence Friedman has called ‘legal culture’: the ensemble of a society’s opinions, expectations and attitudes regarding the law. Through a study of judicial scenes in El matadero by Esteban Echeverría (published in 1871) and Martín Fierro by José Hernández (1872, 1879) in which State notions of criminality and of justice are disputed, I argue that these texts fix a position of literature on the law and State justice that displaces the symbolic place of criminality in society, and establish a site of enunciation specific to Argentine literature that continues to operate into the present.